Analysis of dehesas with multiple use. Physical and economic indexes of sustainable management (BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS, 1998)
The wide surface that dehesas hold in Spain, together with their economic, social and environmental importance, give enough justification to the researchs that widen the scientific knowlege about the economics of dehesa systems. However, the dehesa agroforestry farms do not appear in the different statistical documentary sources of the Agricultural Accounting Net. The lack of technical-economic data about these systems impede neither to observe the effects of the Common Agricultural Policy on the natural environment, nor to know as a whole the dynamics and structure of their flows and the stock of resources and income. This paper deals with the technical and economic management of dehesas in the field of the environmental economics. Its main aim has been to carry out an analytical case study. In order to develop it, four dehesa farms in the Southwest of the Badajoz Province were selected. These farms have collaborated on the development of the Research Project UE CAMAR CT 90-28 ``Technical and economic analysis of dehesa and montado systems{''}. Its importance lies in the basis of the case analysis, with a description of the systems and an identification of the structure and dynamics of their resources, either at physical and economic level.